Semi-continuous cultivation of Chlorella vulgaris using chicken compost as nutrients source: Growth optimization study and fatty acid composition analysis - Tan, X.B. (Elsevier Ltd, 2018)
In the present study, cultivation of Chlorella vulgaris was extensively explored under semi-continuous approach to enhance its growth. The microalgae were cultivated in a photobioreactor supplemented with compost derived from chicken waste as an alternative nutrients source in both batch and semi-continuous cultivations. It was found that Chlorella vulgaris grew well up to 17 cycles of semi-continuous cultivation based on the following conditions for each cycle (3 days per cycle): 30 (v/v) removal of cultivation medium and 0.04 L/L of chicken compost in cultivation medium of pH 3. The average biomass productivity attained through these conditions was 0.0736 g/L/day, which was higher than batch cultivation (0.0568 g/L/day). Besides, the average total lipid content from each cycle under semi-continuous cultivation was maintained in the range of 25â35 wt. The success of lipid extraction from the microalgae biomass was evidenced by the result of Fourier Transform Infrared Red (FT-IR) analysis that revealed lower peak intensity of carbon, especially in the range 2809â3012 cmâ1 after lipid extraction. It was also worthwhile to mention that the fatty acid methyl ester (FAME) compositions of Chlorella vulgaris consisted mainly of C16:0 and C18:3 that were not significantly altered during the semi-continuous cultivation. Both saturated and unsaturated fatty acids in the harvested biomass accounted for approximately 26.3 and 73.3, respectively, within 5 cycles of the cultivation. Â© 2018 Elsevier Ltd